The effect of using Wordwall Game application media in economics subjects on student interest at SMA Negeri 2 Sanga Desa - Lestari, Ayu; Rachmawati, Diana Widhi; Toyib, M Toyib (Institute of Computer Science (IOCS), 2024)
This study identified problems in the teaching and learning process at SMA Negeri 2 Sanga Desa, especially related to student learning difficulties related to personality characteristics and learning habits, as well as students performing below their abilities. The research aims to evaluate the effect of synectic learning media, especially wordwall games, on the learning interest of students in class XI IPS 1 in the subject of economic growth and development. The research method used is the experimental method. The results of the wordwall game test in the experimental class showed an average increase in students of 85.66%. In the synectic model category, student activeness reached an average of 46.66%, and experimental student learning outcomes showed an increase of 46.66%. The overall analysis showed a significant increase in students after applying the wordwall game media of synectical learning, with an average increase of 85.66%, categorized as